Effect of Stimulus Size in a Visual ERP-Based BCI under RSVP - Fernández-Rodríguez, Álvaro; Darves-Bornoz, Aube; Velasco-Álvarez, Francisco Javier; Ron-Angevin, Ricardo (MPDI, 2022)
Rapid serial visual presentation (RSVP) is currently one of the most suitable paradigms for use with a visual brain–computer interface based on event-related potentials (ERP-BCI) by patients with a lack of ocular motility. However, gaze-independent paradigms have not been studied as closely as gaze-dependent ones, and variables such as the sizes of the stimuli presented have not yet been explored under RSVP. Hence, the aim of the present work is to assess whether stimulus size has an impact on ERP-BCI performance under the RSVP paradigm. Twelve participants tested the ERP-BCI under RSVP using three different stimulus sizes: small (0.1 x 0.1 cm), medium (1.9 x 1.8 cm), and large (20.05 x 19.9 cm) at 60 cm. The results showed significant differences in accuracy between the conditions; the larger the stimulus, the better the accuracy obtained. It was also shown that these differences were not due to incorrect perception of the stimuli since there was no effect from the size in a perceptual discrimination task. The present work therefore shows that stimulus size has an impact on the performance of an ERP-BCI under RSVP. This finding should be considered by future ERP-BCI proposals aimed at users who need gaze-independent systems.
Keywords: Electrónica - Tecnología; brain–computer interface (BCI); event-related potential (ERP); rapid serial visual presentation (RSVP); stimulus;; size